2015
DOI: 10.1152/ajprenal.00687.2014
|View full text |Cite
|
Sign up to set email alerts
|

KCNJ10 (Kir4.1) is expressed in the basolateral membrane of the cortical thick ascending limb

Abstract: The aim of the present study is to examine the role of Kcnj10 (Kir.4.1) in contributing to the basolateral K conductance in the cortical thick ascending limb (cTAL) using Kcnj10+/+ wild-type (WT) and Kcnj10−/− knockout (KO) mice. The patch-clamp experiments detected a 40- and an 80-pS K channel in the basolateral membrane of the cTAL. Moreover, the probability of finding the 40-pS K was significantly higher in the late part of the cTAL close to the distal convoluted tubule than those in the initial part. Immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 29 publications
2
58
1
Order By: Relevance
“…First, expression of NCC was analyzed to assess changes in transporters mediating sodium absorption in DCTs. Since it was reported that Kcnj10 is expressed in the cortical part of the thick ascending limb of Henle's loop (TAL) (20,33), we also explored the abundance of the Na…”
Section: Zfn-based Null Mutation Of Kcnj16 In the Ss Ratmentioning
confidence: 99%
“…First, expression of NCC was analyzed to assess changes in transporters mediating sodium absorption in DCTs. Since it was reported that Kcnj10 is expressed in the cortical part of the thick ascending limb of Henle's loop (TAL) (20,33), we also explored the abundance of the Na…”
Section: Zfn-based Null Mutation Of Kcnj16 In the Ss Ratmentioning
confidence: 99%
“…This protein is expressed in several tissues, including the central nervous system, inner ear and basolateral side of DCT cells and possibly also TAL cells (reviewed in [41, 42]). In the kidney it forms a basolateral K + channel that conducts outward K + currents, thus recycling the K + imported by the Na + -K + -ATPase.…”
Section: Hereditary Hypomagnesemiasmentioning
confidence: 99%
“…1C is a scheme showing the expression of NKCC2, NCC, ENaC and ROMK in the apical membrane of the cTAL, DCT and CNT/CCD, respectively. However, experiments performed in post-neonatal 9 day (p9) mice have showed that the expression of Kir4.1 in the cTAL is mainly limited in the late part of cTAL rather than in the whole length of the cTAL of the mouse kidney [27*]. Kir4.1 expression was also detected in human TAL, however, loss-of-function mutations of Kir4.1 in humans did not have phenotype of defective membrane transport in the TAL, suggesting that Kir4.1 function in the TAL may not be indispensable [2123].…”
Section: Expression Of Kir41 Along the Nephron Segmentsmentioning
confidence: 99%
“…Kir4.1 expression was also detected in human TAL, however, loss-of-function mutations of Kir4.1 in humans did not have phenotype of defective membrane transport in the TAL, suggesting that Kir4.1 function in the TAL may not be indispensable [2123]. The possibility that Kir4.1 function in the cTAL could be compensated is also supported by patch-clamp experiments performed in p9 neonatal Kcnj10 −/− mice demonstrating that the disruption of Kir4.1 stimulates the activity of Na + and Cl − -activated 80- to 150-pS K + channel (K ca 4.1 or slo 2.2) in the cTAL [27;28]. The upregulation of Na-activated 80–150 pS K channel in the TAL may be induced by high vasopressin level in p9 neonatal Kir4.1 knockout mice as evidenced by the finding that AQP2 expression was upregulated [29].…”
Section: Expression Of Kir41 Along the Nephron Segmentsmentioning
confidence: 99%